Acetaldehyde and parkinsonism: role of CYP450 2E1 - Vaglini, Francesca; Viaggi, Cristina; Piro, Valentina; Pardini, Carla; Gerace, Claudio; Scarselli, Marco; Corsini, Giovanni U. (Frontiers in Behavioral Neuroscience, 2013)
The present review update the relationship between acetaldehyde and parkinsonism with a specific focus on the role of P450 system and CYP 2E1 isozyme particularly. We have indicated that acetaldehyde is able to enhance the parkinsonism induced in mice by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, a neurotoxin able to damage the nigrostriatal dopaminergic pathway. Similarly diethyldithiocarbamate, the main metabolite of disulfiram, a drug widely used to control alcoholism, diallylsulfide and phenylisothiocyanate also markedly enhance the toxin-related parkinsonism. All these compounds are substrate/inhibitors of CYP450 2E1 isozyme. The presence of CYP 2E1 has been detected in the dopamine neurons of rodent Substantia Nigra, but a precise function of the enzyme has not been elucidated yet. By treating CYP 2E1 knockout mice with the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, the Substantia Nigra induced lesion was significantly reduced when compared with the lesion observed in wild-type animals. Several in vivo and in vitro studies led to the conclusion that CYP 2E1 may enhance the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity in mice by increasing free radical production inside the dopaminergic neurons. Acetaldehyde is a good substrate for CYP 2E1 enzyme as the other substrate-inhibitors and by this way may facilitate the susceptibility of dopaminergic neurons to toxic events. The literature suggests that ethanol and/or disulfiram may be responsible for toxic parkinsonism in human and it indicates that basal ganglia are the major targets of disulfiram toxicity. A very recent study reports that there are a decreased methylation of the CYP 2E1 gene and increased expression of CYP 2E1 mRNA in Parkinson’s Disease patient brains. This study suggests that epigenetic variants of this cytochrome contribute to the susceptibility, thus confirming multiples lines of evidence which indicate a link between environmental toxins and Parkinson’s Disease.